Social media in cardiovascular medicine: A contemporary review - Ladeiras-Lopes, Ricardo; Baciu, Lavinia; Grapsa, Julia; Sohaib, Afzal; Vidal-Perez, Rafael; Bohm, Allan; Silvola, Harri; Gimenez, Maria Rubini; Muscoli, Saverio; Wallner, Markus; Rakisheva, Amina; Nagy, Vivien Klaudia; et al. (European Heart Journal – Digital Health, 2020)
Social media increasingly impact both the private and professional lives of the majority of the population, including individuals engaged in cardiovascular healthcare and research. Healthcare providers across the world use social media platforms such as Twitter or Facebook to find medical and scientific information, to follow scientific meetings, to discuss individual clinical cases with colleagues, and to engage with patients. While social media provide a means for fast, interactive and accessible communication without geographic boundaries, their use to obtain and disseminate information has limitations and the potential threats are not always clearly understood. Governance concerns include a lack of rigorous quality control, bias due to the pre-selection of presented content by filter algorithms, and the risk of inadvertent breach of patient confidentiality. This article provides information and guidance regarding the role and use of social media platforms in cardiovascular medicine, with an emphasis on the new opportunities for the dissemination of scientific information and continuing education that arise from their responsible use.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Cardiovascular medicine; Cardiovascular science; Digital health; e-Cardiology; Social media